2018
DOI: 10.1155/2018/8720101
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Infection and Periodontal Disease: Is there a Common Immunological Link?

Abstract: Hepatitis C virus (HCV) infections could have an important impact on the oral health status of patients, favoring conditions such as periodontal disease and oral cancer. The review of the existing scientific literature written in English was performed, searching for oral and periodontal manifestations of HCV infection and its impact on the oral fluids. HCV infection can determine direct extrahepatic manifestations at the oral and periodontal level including oral lichen planus, Sjögren-like sialadenitis, and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…As it has been previously suggested [68,75,76], the possible connection between periodontal disease and chronic hepatitis C becomes more than plausible. It seems that, given the holistic perspective on the pathogenic mechanisms of the human body, any disruption of its homeostasis caused by inflammatory processes ongoing even in distant territories like the periodontal and liver tissues has a general impact that reverberates across the entire biological structure and becomes relevant in terms of clinical manifestation.…”
Section: Connections Between Hcv Infection and Periodontal Statusmentioning
confidence: 93%
See 2 more Smart Citations
“…As it has been previously suggested [68,75,76], the possible connection between periodontal disease and chronic hepatitis C becomes more than plausible. It seems that, given the holistic perspective on the pathogenic mechanisms of the human body, any disruption of its homeostasis caused by inflammatory processes ongoing even in distant territories like the periodontal and liver tissues has a general impact that reverberates across the entire biological structure and becomes relevant in terms of clinical manifestation.…”
Section: Connections Between Hcv Infection and Periodontal Statusmentioning
confidence: 93%
“…This can leave the patient vulnerable to the onset of other infections such as periodontal disease triggered by bacterial biofilm. Recent scientific data show that multiple-layered connections between HCV infection and periodontal disease could be possible, including transmission implications via oral fluids (saliva and gingival fluid), related clinical manifestations of the two conditions [63,[67][68][69], and common pathogenic pathways that may favor their evolution [68].…”
Section: Connections Between Hcv Infection and Periodontal Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some authors suggested that, HCV may lead to the development of SS 47 .The Sjogren's Sydnrome (SS) is associated with marked reduction in saliva flow into the oral cavity leading to, dryness of oral cavity and subsequently, the teeth no longer protected against bacteria by salivary components and the dental plaque are no longer removed by the saliva flow. This dryness of mouth leading to dental caries and fragile oral mucosa which becomes more susceptible to trauma and infection 41 The direct infection and proliferation of HCV in salivary glands together with formation of immune complexes containing HCV may explain the association between the SS and HCV infection 48,49…”
Section: Oral Diseases Related To Hepatitis C Virus Infectionmentioning
confidence: 99%
“…The periodontal changes for HCV patients occur more frequently and more visible than for healthy control group. Several pathological changes boost proinflammatory cytokines production [19,20]. Periodontal disease occurs when the ecological balance of the oral cavity is disrupted and periodontal bacterial pathogens start triggering an inflammatory reaction.…”
Section: Introductionmentioning
confidence: 99%